Ectopic Pregnancy - A 3 Year Analysis Of Different Presentations At Tertiary Care Hospitals Of Karachi. - Samina Kemal; Rubina Hussain; Shama Chaudhry (ziauddin University, 2024)
Background: Ectopic pregnancy is a global problem and is the most common life-threatening emergency in early pregnancy leading to significant morbidity and fetal loss. It occurs in variable presentations. The main objective is to study the prevalence, risk factors and management of cases of ectopic pregnancies at tertiary care hospitals over a three year time period. Methods: This is a retrospective study of cases of ectopic gestations managed in tertiary care Hospital Karachi from July 2013 to July 2016. Information was taken from case notes, theater and labor ward registers, and the cases what we managed. Results: During the study period, we admitted total number of 3113 gynecology cases from 2013 to 2016 out of which 76 pregnancies turned out to be ectopic pregnancies with different presentations. Majority of these presented at the age group of 20-30 years and found more in primigravida. History of infertility was found to be the highest risk factor and tubal pregnancy remained the most common site of ectopic pregnancy. Conclusion: Ectopic pregnancy is a major challenge in gynecological practice and was found more in primigravida. Most of the cases usually present late that makes the tubal conservation treatment inapplicable. Use of modern diagnostic techniques by the clinicians will assist in early diagnosis and treatment prior to tubal rupture which will ultimately lead to reduction in maternal morbidity and mortality associated with the condition Key Words: Ectopic pregnancy, tubal pregnancy, mortality, B- HCG